Evaluation of factors affecting agricultural cooperatives performance in Malaysia - Idris, Nurjihan; Abdullah, Amin Mahir (2011)
Malaysia targets cooperatives sector to be the third engine of economic development in the 9th Malaysian plan and to increase its contribution to 5% of Malaysian GDP in 2013 from 1% in 2008. This study investigates factors that affect performance of agricultural cooperatives in Malaysia. Production function is used as a guide to measure how much input (farm size, share capital, labor and energy cost) is needed to produce goods and services (sales). Panel data analysis or random effect model in particular is used to measure economic efficiency of agricultural cooperatives. The data used is from yearly financial report of Malaysian agricultural cooperative from 2004-2007. The result indicates that only labor is significant in determining sales of cooperatives.